2016
DOI: 10.1177/0885328215626072
|View full text |Cite
|
Sign up to set email alerts
|

Plasma functionalization of polycarbonaturethane to improve endothelialization—Effect of shear stress as a critical factor for biocompatibility control

Abstract: Medical devices made of polycarbonaturethane (PCU) combine excellent mechanical properties and little biological degradation, but restricted hemocompatibility. Modifications of PCU might reduce platelet adhesion and promote stable endothelialization. PCU was modified using gas plasma treatment, binding of hydrogels, and coupling of cellactive molecules (modified heparin, anti-thrombin III (ATIII), argatroban, fibronectin, laminin-nonapeptide, peptides with integrin-binding arginine-glycine-aspartic acid (RGD) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 61 publications
1
9
0
Order By: Relevance
“…Chemical modifications have been used to improve the hemocompatibility of Chronoflex AR as a potential material for the pump chamber of implantable VAD systems [20]. Among the modified PCU samples used in the present study, PEI-AT modification had minor effects on mechanical properties and showed increased wettability, reduced bacterial cell binding, suppressed platelet adhesion and activation, and activation of complement and coagulation under shear stress.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…Chemical modifications have been used to improve the hemocompatibility of Chronoflex AR as a potential material for the pump chamber of implantable VAD systems [20]. Among the modified PCU samples used in the present study, PEI-AT modification had minor effects on mechanical properties and showed increased wettability, reduced bacterial cell binding, suppressed platelet adhesion and activation, and activation of complement and coagulation under shear stress.…”
Section: Discussionmentioning
confidence: 96%
“…The details on handling and modifying the PCU discs and helical grafts have been described previously [20]. Chemicals were obtained from Merck (Darmstadt, Germany) or Sigma-Aldrich (Munich, Germany), unless noted otherwise.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations